Pigmentation, Melanocyte Colonization, and p53 Status in Basal Cell Carcinoma. (16th September 2010) - Frey, Lídia M.; Houben, Roland; Bröcker, Eva-B.
Abstract : Basal cell carcinoma (BCC) is the most common neoplasm in the Caucasian population. Only a fraction of BCC exhibits pigmentation. Lack of melanocyte colonization has been suggested to be due to p53-inactivating mutations in the BCC cells interfering with the p53-proopiomelanocortin pathway and the production of alpha melanocyte-stimulating hormone in the tumor. To evaluate this, we determined tumor pigmentation as well as expression of melan-A and of p53 in 49 BCC tissues by means of immunohistochemistry. As expected, we observed a positive relation between tumor pigmentation and melan-A positive intra-tumoral melanocytes. Melanocyte colonization and, to a lesser extent, p53 overexpression showed intraindividual heterogeneity in larger tumors. p53 overexpression, which is indicative of p53 mutations, was not correlated to melanocyte colonization of BCC. Sequencing of exon 5–8 of the p53 gene in selected BCC cases revealed that colonization by melanocytes and BCC pigmentation is neither ablated by p53 mutations nor generally present in BCCs with wild-type p53.